A financial feasibility study: Constructing unit train capabilities to access the Pacific Northwest export market - Horn, Kevin (My University, 2020)
This study focuses on export grain merchandising opportunities for an upper Mississippi River barge terminal (MRBT) centrally located to corn and soybean (grain) production areas in Wisconsin and Minnesota. The main channels for exporting grain from the U.S. are the Pacific Northwest (PNW) and New Orleans, Louisiana (NOLA). Presently, MRBT only has capability to transport grain by barge to NOLA for export. There are a number of challenges associated with relying on barge transportation and having a single export channel. Building another form of transportation to access a secondary export market could mitigate return associated with the first channel and create additional revenue. The purpose of this study is to examine the financial feasibility of adding shuttle train loading capabilities to MRBT. This paper analyzes grain cost indicators, compares NOLA and PNW grain export prices with respect to MRBT, and compares MRBT competitive logistics with respect to barge and shuttle rail transportation methods. The findings indicated there was a positive net present value and identified several synergies from upgrading MRBT to be shuttle capable. Expanding access to the PNW could provide long-term economic advantages for future growth in a low margin industry.
Keywords: Feasibility; Pacific Northwest; Export; Agricultural Economics